Analysis of sleep in individual Drosophila melanogaster reveals a self‐regulatory role for cuticular hydrocarbons pheromones. (14th March 2022) - Wu, Xiaoyu; Wang, Su; Zhao, Xianguo; Wen, Jing; Li, Yahong; Zhao, Zhangwu; Du, Juan
Abstract: It is well established that pheromones are used by insects to transmit information between individuals. However, research has revealed that individual insects can be both the sender and the receiver of some pheromonal signals. It is therefore interesting to consider whether the pheromonal state of an individual insect can exert an effect on itself. In this study, we monitored the sleep activity of single flies exhibiting a mutation that leads to pheromonal deficiency and found that cuticular hydrocarbons (CHs) exerted self‐regulatory effects on the amount of sleep experienced by these flies. To identify the physiological significance of this mechanism, we compared the amounts of sleep in individual young flies and individual old flies (flies are known to sleep less as they get older) and compared this data with young and old flies exhibiting mutations that lead to CH reception defects. The differences in the amount of sleep experienced by young and old mutant flies were significantly lower than those of the control flies. Our data show that hydrocarbon signals produced by the cuticle in Drosophila can be self‐perceived and regulate the amount of sleep acquired in a maturation‐dependent manner. Abstract : The sleep amount of individual Drosophila melanogaster with defects in production or reception of Cuticular hydrocarbons (CHs) is increased. while, over expression of the enzyme that is important in CHs production results in sleep loss for individual Drosophila melanogaster. This result indicated a self‐regulatory role for cuticular hydrocarbons pheromones.